Entomofauna associated with erva-de-touro (Poiretia latifolia Vogel) stands in the Santa Catarina plateau region (Revista de Ciências Agroveterinárias, 2018)
Poiretia latifolia Vogel (Fabaceae), a native plant of the high-altitude field ecosystems appears to show promise, when introduced into the Atlantic Forest biome of southern Brazil. It is valued for its monoterpene-rich essential oil and exhibits great potential in the pharmaceutical and cosmetic industries. This work aimed at studying the entomofauna associated with P. latifolia, as well as assessing the effects of these insects on this plant's reproductive success. The entomofauna were surveyed between December 2015 and January 2016, in two natural P. latifolia stands found in the Capão Alto and São José do Cerrito municipalities of Santa Catarina State. At each site, the entomofauna were subjected to 42-hour monitoring periods and five marked plants in each area were monitored every hour, from 9:00 am to 4:00 p.m. The effects of the climatic variables on the insect were analyzed using the Pearson correlation coefficient. To determine the damage due to herbivory, ten P. latifolia plants were marked at each site, from which the flowers and seeds were collected and the insect damage estimated. The predominant insects in both stands were identified as belonging to the orders Coleoptera, Diptera and Hymenoptera. The Dipteran insects revealed a significant positive correlation with the mean daily temperature (r = 0.84, p = 0.03442) in the Capão Alto stand. Damages caused by insects to the P. latifolia flowers and seeds were 54% and 88%, respectively, and were even higher in the São José do Cerrito area. Environmental changes precipitated by the intense agricultural usage in the vicinity of the P. latifolia stands may have been the reason for these differences.
Keywords: faunistic analysis; florivory; seed predation; Fabaceae; altitude fields; ecosystem